External Validation of the ASSURE Model for Predicting Oncological Outcomes After Resection of High-risk Renal Cell Carcinoma (RESCUE Study: UroCCR 88) - Zine-Eddine Khene; Alessandro Larcher; Jean-Christophe Bernhard; Nicolas Doumerc; Idir Ouzaid; Umberto Capitanio; François-Xavier Nouhaud; Romain Boissier; Nathalie Rioux-Leclercq; Alexandre De La Taille; Philippe Barthelemy; Francesco Montorsi; et al. (European Urology Open Science, 2021)
A prognostic model based on the population of the ASSURE phase 3 trial has recently been described. The ASSURE model stratifies patients into risk groups to predict survival after surgical resection of intermediate- and high-risk localised kidney cancer. We evaluated this model in an independent cohort of 1372 patients using discrimination, calibration, and decision curve analysis. Regarding disease-free survival, the ASSURE model showed modest discrimination (65%), miscalibration, and poor net benefit compared with the UCLA Integrated Staging System (UISS) and Leibovich 2018 models. Similarly, the ability of the ASSURE model to predict overall survival was poor in terms of discrimination (63%), with overestimation on calibration plots and a modest net benefit for the probability threshold of between 10% and 40%. Overall, our results show that the performance of the ASSURE model was less optimistic than expected, and not associated with a clear improvement in patient selection and clinical usefulness in comparison to with available models. We propose an updated version using the recalibration method, which leads to a (slight) improvement in performance but should be validated in another external population. Patient summary: The recent ASSURE model evaluates survival after surgery for nonmetastatic kidney cancer. We found no clear improvement in patient classification when we compared ASSURE with older models, so use of this model for patients with nonmetastatic kidney cancer still needs to be clarified.